Sesame and cardiovascular balance: a GRADE-assessed systematic review and meta-analysis of its role in modulating risk factors among individuals with prehypertension and hypertension - Mardani, Helia; Ghalichi, Faezeh; Fashtali, Zahra Mirzaei; Ardakany, Sara Jamei; Yousefabady, Matin Abdollahi; Mohajerani, Arefeh; Musazadeh, Vali; Jafari, Ali (Clinical hypertension, 2025)
This systematic review aimed to evaluate the clinical effectiveness of sesame supplementation on cardiovascular health parameters in pre-hypertensive and hypertensive individuals. A systematic search was conducted up to August 2024.Eligible studies evaluated the effects of sesame supplementation on blood pressure, anthropometric indices, lipid profiles, and oxidative stress markers. Study quality and evidence strength were assessed using the Cochrane Risk of Bias tool and the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach, respectively. Six trials, with interventions ranging from 4 to 8 weeks and involving 465 participants, reported reductions in body mass index (weighted mean difference [WMD], -3.00 kg/m ; 95% confidence interval [CI], -3.43 to -2.57; < 0.001), weight (WMD, -7.51 kg; 95% CI, -8.64 to -6.37; < 0.001), diastolic blood pressure (WMD, -16.29 mmHg; 95% CI, -25.37 to -7.22; < 0.001), systolic blood pressure (WMD, -20.78 mmHg; 95% CI, -32.26 to -9.31; < 0.001), high-density lipoprotein cholesterol (WMD, 2.21 mg/dL; 95% CI, 0.09 to 4.33; = 0.041), total cholesterol (WMD, -49.29 mg/dL; 95% CI, -96.71 to -1.86; = 0.042), triglycerides (WMD, -55.05 mg/dL; 95% CI, -79.51, -30.59; < 0.001), catalase (WMD, 3.38 U/mg of protein; 95% CI, 3.24 to 3.52; < 0.001), erythrocyte glutathione peroxidase (WMD, 0.93 U/min/mg of hemoglobin [Hb]; 95% CI, 0.38 to 1.47; = 0.001), erythrocyte superoxide dismutase (WMD, 3.11 U/ mg of Hb; 95% CI, 2.92 to 3.29; < 0.001), and thiobarbituric acid reactive substances (WMD, -2.94 nmol/dL; 95% CI, -3.99 to -1.89; < 0.001). In contrast, no significant effects were observed on low-density lipoprotein cholesterol or malondialdehyde). However, the GRADE assessment rated the evidence as very low across all outcomes due to high heterogeneity, small sample sizes, and methodological limitations, rendering the clinical plausibility of these findings uncertain. While sesame supplementation showed apparent improvements in several cardiovascular risk factors, the very low certainty of evidence, driven by study limitations and implausible effect sizes, precludes definitive conclusions. High-quality, well-designed randomized controlled trials are needed to clarify sesame's therapeutic role in prehypertension and hypertension. PROSPERO Identifier: CRD42025634033.